Tsunami Hazard Evaluation in Temon Sub-district, Kulon Progo Regency Based on the Worst-Case Scenario of the South Java Megathrust Earthquake - Nana Dyana; Yohana Noradika Maharani; Suharsono; Arif Rianto Budi Nugroho; Tedy Agung Cahyadi (Berkala Sainstek)
Kapanewon Temon, the location of New Yogyakarta International Airport (NYIA), is projected to become a new economic center but is vulnerable to tsunami hazards due to its proximity to the southern Java subduction zone. Mitigation efforts are necessary to prepare for the worst-case scenarios. This study assesses tsunami hazard potential based on a worst-case scenario using a geophysical approach through numerical simulations with the COMCOT software. The data used include bathymetry, topography, administrative boundaries, land cover, and fault parameters. Simulation results indicate potential tsunami inundation up to 20 meters in key areas such as Congot Beach, the southern coast of NYIA, and Glagah Beach, with an estimated arrival time of 0.6-0.63 hours. These findings are expected to serve as a reference for spatial planning and disaster risk mitigation efforts in Kapanewon Temon, Kulon Progo Regency.